Educational Management Strategies for Enhancing Access and Quality of Education for Students in Remote Areas - Siminto; Qodir, Abdul; Choerudin, Achmad (PT. LITERASI SAINS NUSANTARA, 2024)
Education is a fundamental pillar in the development and progress of a country, playing a crucial role in improving the quality of human resources and promoting sustainable economic growth. However, in many remote areas, access to and the quality of education often face significant challenges. This study aims to explore and analyze various educational management strategies that can be implemented to enhance access and quality of education in these areas. The research employs a literature review method with a qualitative descriptive analysis approach. The primary data sources for this study were obtained from Google Scholar, focusing on articles published between 2008 and 2024. The findings reveal that improving access to and the quality of education in remote areas requires a comprehensive and integrated educational management approach. Limitations in infrastructure, lack of access to technology, and inadequate teacher skills are the main challenges that need to be addressed. The case studies discussed indicate that the use of technology, investment in infrastructure, teacher training, and collaboration among government, educational institutions, and local communities can provide effective solutions. Supportive policies and community-based development models have also proven to contribute to the improvement of educational quality. Therefore, effective educational management strategies must encompass these various aspects to achieve optimal outcomes.